El método fenomenológico como posibilidad de integración entre ética y ontología - González, Carmen (ARFIL y UNL, 2018)
The present paper is an attempt to show how experience, as a fundamental moment of the phenomenological method, allows for the recuperation of the linkage between the subject and the world that modern idealism had questioned. It is pointed out as well, that, in Husserl’s philosophy as in Hegel’s, this very experience has a load, perhaps excessive, of emotionality in one case, and of intellective activity in the other, but both separated from each other. This disengagement of the two instances that integrate the cognitive experiential processes —affection and intellection— prevents the definite step towards the linkage between ethics and ontology. Finally, we show how, in Karol Wojtyla’s philosophy, it is possible to overcome this separation, from the recovering of the moment of self-experience, and thus, it is possible to raise again the issue about the relation between ethics and ontology.